Spinal and Paraspinal Fungal Infections Associated With Contaminated Methylprednisolone Injections. (14th May 2014) - Moudgal, Varsha; Singal, Bonita; Kauffman, Carol A.; Brodkey, Jason A.; Malani, Anurag N.; Olmsted, Russell N.; Kasotakis, Michael J.; Koch, Spencer R.; Kaakaji, Rami; Nyaku, Mawuli; Neelakanta, Anupama; Valenstein, Paul; et al.
Abstract: Background.  A nationwide outbreak of fungal infections was traced to injection of Exserohilum -contaminated methylprednisolone . We describe our experience with patients who developed spinal or paraspinal infection after injection of contaminated methylprednisolone. Methods.  Data were assembled from the Michigan Department of Community Health, electronic medical records, and magnetic resonance imaging (MRI) reports. Results.  Of 544 patients who received an epidural injection from a contaminated lot of methylprednisolone at a pain clinic in southeastern Michigan, 153 (28%) were diagnosed at our institution with probable or confirmed spinal or paraspinal fungal infection at the injection site. Forty-one patients had both meningitis and spinal or paraspinal infection, and 112 had only spinal or paraspinal infection. Magnetic resonance imaging abnormalities included abscess, phlegmon, arachnoiditis, and osteomyelitis. Surgical debridement in 116 patients revealed epidural phlegmon and epidural abscess most often. Among 26 patients with an abnormal MRI but with no increase or change in chronic pain, 19 (73%) had infection identified at surgery. Fungal infection was confirmed in 78 patients (51%) by finding hyphae in tissues, positive polymerase chain reaction, or culture. Initial therapy was voriconazole plus liposomal amphotericin B in 115 patients (75%) and voriconazole alone in 38 patients (25%). As of January 31, 2014, 20 patients remained on an azole agent. Five patients died of infection. Conclusions.  We report on 153 patients who had spinal or paraspinal fungal infection at the site of epidural injection of contaminated methylprednisolone. One hundred sixteen (76%) underwent operative debridement in addition to treatment with antifungal agents.